2015
DOI: 10.1063/1.4905543
|View full text |Cite
|
Sign up to set email alerts
|

Model for temperature-dependent magnetization of nanocrystalline materials

Abstract: A magnetization model of nanocrystalline materials incorporating intragrain anisotropies, intergrain interactions, and texture effects has been extended to include the thermal fluctuations. The method relies on the stochastic Landau–Lifshitz–Gilbert theory of magnetization dynamics and permits to study the magnetic properties of nanocrystalline materials at arbitrary temperature below the Currie temperature. The model has been used to determine the intergrain exchange constant and grain boundary anisotropy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…The unusual thermal softening of anisotropy constitutes a key feature of the present NWs. Many studies reported on variations of anisotropy with temperature, related to a variation of physical constants, such as magnetocrystalline constants [48]. In the present work, the samples show a similar shift of the anisotropy distribution, over different temperature ranges until 150 K. This suggests a general thermally activated process and not the thermal variation of a constant that would impact the samples differently as a function of temperature.…”
Section: Thermal Softening Of Anisotropysupporting
confidence: 70%
“…The unusual thermal softening of anisotropy constitutes a key feature of the present NWs. Many studies reported on variations of anisotropy with temperature, related to a variation of physical constants, such as magnetocrystalline constants [48]. In the present work, the samples show a similar shift of the anisotropy distribution, over different temperature ranges until 150 K. This suggests a general thermally activated process and not the thermal variation of a constant that would impact the samples differently as a function of temperature.…”
Section: Thermal Softening Of Anisotropysupporting
confidence: 70%
“…5a, we could obtain both qualitative and quantitative description of the experimental data by using typical values of saturation magnetization (M S = 1.4 MA m −1 ) and adjusting the exchange stiffness to take into account an effective room temperature exchange across the nanocrystalline structure (A ex = 17.5 pJ m −1 ). 40,41 In addition, we have tested the role of the magnetocrystalline anisotropy repeating the simulation with and without a random anisotropy model (RAM), including a grainy structure (10 nm grains) with typical intrinsic magnetocrystalline anisotropy (K = 520 kJ m −3 ) 42 and random distribution of easy axis. In both cases (with and without the use of RAM), we get the same results for both stressed and unstressed systems.…”
Section: Resultsmentioning
confidence: 99%